Analysis of the Economic Potential of Porang Plants and Porang Content Creator Through the YouTube Platform - Maemunah Nurmaya Sari; Andri Waskito; Saripah Saripah (Universitas Indraprasta PGRI, 2022)
The Porang plant has recently gained popularity due to its high selling value and has become a superior export commodity that is in demand by many countries. The data shows that there is a significant increase in searches with the keyword